2017
DOI: 10.3892/or.2017.5464
|View full text |Cite|
|
Sign up to set email alerts
|

miR-9 regulates the multidrug resistance of chronic myelogenous leukemia by targeting ABCB1

Abstract: Multidrug resistance (MDR) is commonly correlated with the poor prognosis of chronic myelogenous leukemia. Aberrant expression of microRNAs (miRNAs) plays an important role in the MDR of various types of cancers. MicroRNA-9 (miR-9) has been confirmed to be dysregulated in many types of cancers. However, the relationship between miR-9 and MDR in chronic myelogenous leukemia (CML) remains largely unknown. In the present study, we showed that miR‑9-3p (miR-9) was downregulated in adriamycin (ADR)‑resistant K562/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Since ERRα can regulate the mRNA stability of ABCB1, we then investigated whether miRNAs were involved in this process. The expression of miR‐9, miR‐200c, miR‐206, and miR‐495 was investigated in cells treated XCT‐790 due to they can directly bind to 3′UTR of ABCB1 to regulate its stability. Our data showed that XCT‐790 can increase the expression of miR‐9, while not others, in both MG‐63/Dox (Figure A) and HOS/Dox (Figure B) cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since ERRα can regulate the mRNA stability of ABCB1, we then investigated whether miRNAs were involved in this process. The expression of miR‐9, miR‐200c, miR‐206, and miR‐495 was investigated in cells treated XCT‐790 due to they can directly bind to 3′UTR of ABCB1 to regulate its stability. Our data showed that XCT‐790 can increase the expression of miR‐9, while not others, in both MG‐63/Dox (Figure A) and HOS/Dox (Figure B) cells.…”
Section: Resultsmentioning
confidence: 99%
“…Various miRNAs such as miR‐9, miR‐200c, miR‐206, and miR‐495 can regulate the expression of ABCB1 in cancer cells. It has been confirmed by luciferase activity analysis that miR‐9 can direct bind to the 3′UTR of ABCB1 and then trigger its decay in cancer cells . As a transcription factor, ERRα might occupy the conserved ERRE in the promoter of miRNAs and then regulate their expression .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al . [82] , 2017 ABCC1 miR-1291 pancreatic cancer, lung cancer, kidney doxorubicin Pan et al . [88] , 2013…”
Section: K562 Cell Line Adriamycinmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small non-coding RNA recently implicated in numerous biological processes through via regulating gene expression (5)(6)(7). Accumulating studies have reported the aberrant expression and key roles of several miRNAs in CML (8)(9)(10)(11)(12). Exploration of key miRNAs associated with CML development has become a hot topic of research.…”
Section: Introductionmentioning
confidence: 99%